2015
DOI: 10.1002/aic.15111
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of biomass char gasification in a downdraft reactor for syngas production

Abstract: A steady state, one-dimensional computational fluid dynamics model of wood char gasification in a downdraft reactor is presented. The model is not only based on reaction kinetics and fluid flow in the porous char bed but also on equations of heat and mass conservation. An original OpenFOAM solver is used to simulate the model and the results are found to be in good agreement with published experimental data. Next, a sensitivity analysis is performed to study the influence of reactor inlet temperature and gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…: Syngas composition for poplar wood and PE under N2, steam and CO2 [118] and H2 from char [123]. A simulation analysis by Ephraim, (2016 b ) [150] provides insight into the evolution of the complex reaction mechanisms along the char bed of a downdraft gasifier under varying concentrations of mixed reaction atmospheres (O2, H2O and CO2). Their results have shown that the reaction atmosphere strongly influences the gasification reaction rates in the gasifier entrance zone, whereby the increase in O2 concentration (0 to 3 vol%) strongly increases the rates of combustion, steam gasification, Boudouard and WGS reactions, whereas increasing H2O (5 to 20 vol%) raises only steam gasification and WGS rates.…”
Section: Gasifying Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…: Syngas composition for poplar wood and PE under N2, steam and CO2 [118] and H2 from char [123]. A simulation analysis by Ephraim, (2016 b ) [150] provides insight into the evolution of the complex reaction mechanisms along the char bed of a downdraft gasifier under varying concentrations of mixed reaction atmospheres (O2, H2O and CO2). Their results have shown that the reaction atmosphere strongly influences the gasification reaction rates in the gasifier entrance zone, whereby the increase in O2 concentration (0 to 3 vol%) strongly increases the rates of combustion, steam gasification, Boudouard and WGS reactions, whereas increasing H2O (5 to 20 vol%) raises only steam gasification and WGS rates.…”
Section: Gasifying Agentmentioning
confidence: 99%
“…Furthermore, CO2 (5 to 20 vol%) only affects Boudouard and WGS reaction rates. Based on their analysis, Ephraim, (2016 b ) [150] concluded that O2 and H2O atmospheres exert the most influence on the syngas composition (H2/CO ratio). Figure 9 gives the syngas composition for poplar wood and PE under N2, steam, and CO2 [118].…”
Section: Gasifying Agentmentioning
confidence: 99%
“…In addition, plastic polymers have been attempted for conversion into useful compounds through pyrolysis, gasification of thermal oxidation ( Ephraim et al, 2016 ). Nanda et al ( Li et al, 2022 ) reviewed the thermochemical conversion (e.g., including pyrolysis, gasification, and liquefaction) of plastic waste to fuels, and concluded that pyrolysis was by far the most widely researched conversion technology compared to liquefaction and gasification.…”
Section: Management Strategies Of Covid-19 Plastic Wastesmentioning
confidence: 99%
“…Co-gasification is widely adopted for the disposal of biomass and clean utilization of coal. It could not only inhibit the generation of SO x and NO x , but also reduce the emission of greenhouse gases [7,[15][16][17][18]. Coal has the advantages of high energy density and high calorific value, while the combustion of coal may lead to serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%